HUDUD INVESTITSION SALOHIYATINI BOSHQARISHDA MARKETING METODOLOGIYASINI TAKOMILLASHTIRISH (Marketing Journal, 2026)
AbstractThis article examines the theoretical and methodological aspects of applyingmarketing approaches in the effective management of a regionʼs investment potential.The role of the territorial marketing concept in enhancing investment attractiveness isrevealed, and scientific proposals and recommendations are developed to improve themechanisms for assessing, forming, and managing investment potential.Keywords: territorial marketing, investment potential, investment attractiveness,marketing strategy, territorial branding, investment climate, investment potential,investment activity, regional economy, exogenous and endogenous factors ofeconomic growth in the region.